(untitled) (Research, Society and Development, 2021)
Introduction: Advertising is present in different moments of our daily lives, as we are continually affected, throughout our lives, by advertisements for products and services that may be able to satisfy our needs and stir our desires. Objective: The objective was to identify evidence in the scientific literature regarding the possible influence of food advertising associated with children’s eating habits. Methodology: This is an integrative literature review article. The search for articles was performed in electronic databases: Scientific Electronic Library Online (SciELO), National Library of Medicine (PubMED) and Latin American and Caribbean Literature on Health Sciences Information (LILACS), in a time frame of 2019 to 2021. Descriptors were used in Portuguese: “Food behavior”, “child”, “food” and in English: “Eating behavior”, “child”, “food”, duly registered in the Health Science Descriptors (DeCS). Results and discussion: The influences of advertising on children’s eating habits and lifestyle were identified, since the programs promote food products using attractive tools, such as drawings. Final considerations: It is also noticed that some foods are marketed with small toys or packaging, arousing even more the desire for products that mostly have low or no nutritional value.